Análisis Jurídico y Comparado de los derechos constitucionales de las personas con discapacidad en Ecuador, Chile y España - Jiménez Armijos, María Magdalena (2023)
This Curricular Integration Work is entitled: "Legal and comparative analysis of the rights of persons with disabilities in Ecuador, Chile and Spain". It arises from the lack of compliance with the constitutional rights of persons with disabilities guaranteed in Article 47 of the Constitution of the Republic of Ecuador. In the past, people with disabilities were marginalized and mistreated due to ignorance and the belief that they were religious punishments. As time progressed, the rights of persons with disabilities were recognized in the 2008 Constitution of Ecuador, considering them as a group of priority attention and guaranteeing a series of rights in areas such as health, education, employment and housing. However, despite these legal guarantees, the State has not fully complied with specialized care, rehabilitation, access to employment and inclusive education for persons with disabilities. The lack of adequate medical care, medical centers without sufficient supplies, no specialized professionals, the absence of rehabilitation programs, employment discrimination in both the public and private sectors, and the lack of infrastructure and specialized services in education are some of the challenges faced by persons with disabilities in Ecuador. That is, despite the fact that rights are guaranteed through the Constitution, this goes beyond reality, since cases of discrimination and inequality are constantly increasing, resulting in the violation of these rights. Similar challenges persist in Chile, such as infrastructure, access and transportation problems, which hinder labor and educational inclusion. Although there are organizations and foundations working to overcome these barriers, and they have been visualized in reality. In contrast, Spain has made greater progress in the inclusion of people with disabilities, thanks to its economic development and the implementation of specialized programs and services. The country has higher employment rates for people with disabilities, as well as inclusive infrastructure and specialized health and education services.